On Insurance Claims Liability PT Jamkrindo - Junnytte Juliana Pinca; Tutiek Retnowati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
The purpose of this research is to find out and analyze whether a fictitious credit agreement that has been Guarantee d by insurance can make a payment claim and to find out and analyze what is the responsibility of PT Jamkrindo for the credit insurance Guarantee of PT Bank Jateng Blora Branch against the fictitious credit of PT Lentera Emas Raya. The research method used is a normative method based on a case study and literature by collecting legal materials, both primary legal materials and secondary legal materials. The legal materials include books, laws and regulations such as the statute approach and conceptual approach. Research results In a fictitious credit agreement that has been Guarantee d by insurance to be able to make a payment claim, it does not have to be a payment claim, against the insurance claim submitted by the policy holder of PT Bank Jateng Blora branch as a creditor to PT. Lentera Emas Raya to PT Jamkrindo as the guarantor cannot be held responsible due to an unlawful act and has violated the terms of the insurance agreement.